1979
DOI: 10.1111/j.1365-2184.1979.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON THE MECHANISM OF HAEMOPOIETIC STEM CELL (CFUs) MOBILIZATION

Abstract: A variety of substances can mobilize haemopoietic stem cells (CFUs) into the peripheral blood. In this study the involvement of the complement system in the mobilization process was investigated. Pretreatment of mice with the complement‐activating factor of cobra venom (CoF), which lowered the serum C3 levels to 10–25% of the normal value, could completely prevent CFUs mobilization induced by high doses of CoF, endotoxin (ET) from Salmonella typhosa, inulin, zymosan and the proteolytic enzymes proteinase and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Moreover, a variety of mediators have been associated with mobilization that seemingly have very little in common, and where the molecular mechanics are sometimes poorly defined. These include sympathomimetics (77, 78), cannabinoid receptor agonists (79), complement (52, 53), elevated lipoprotein levels (80), defibrotide (81), glycosaminoglycans (82), and endotoxin (83). None of these have gained any clinical relevance, but the abundance of mobilizing agents indicates the precariousness of the equilibrium between marrow retention and egress, and may in the future support the rational development of mobilizing strategies for poorly mobilizing patients, or for individuals who are intolerant to G-CSF.…”
Section: G-csf-enhancing and Alternative Activities In Mobilizationmentioning
confidence: 99%
“…Moreover, a variety of mediators have been associated with mobilization that seemingly have very little in common, and where the molecular mechanics are sometimes poorly defined. These include sympathomimetics (77, 78), cannabinoid receptor agonists (79), complement (52, 53), elevated lipoprotein levels (80), defibrotide (81), glycosaminoglycans (82), and endotoxin (83). None of these have gained any clinical relevance, but the abundance of mobilizing agents indicates the precariousness of the equilibrium between marrow retention and egress, and may in the future support the rational development of mobilizing strategies for poorly mobilizing patients, or for individuals who are intolerant to G-CSF.…”
Section: G-csf-enhancing and Alternative Activities In Mobilizationmentioning
confidence: 99%
“…Studies reported over 20 years ago first showed that depletion of C in mice with cobra venom (CoF), which lowered serum C3 levels to 10-25% of normal values, completely prevented CFU-S mobilization induced by endotoxin. 52 Our recent report demonstrated that mice deficient in either C3 or C3aR were more sensitive to mobilization by G-CSF than were WT mice, and that mobilization in WT animals could be increased by employing a C3aR antagonist. 38 Moreover, an anti-CR3 mAb has been reported to enhance mobilization in mice, suggesting an involvement of the iC3b-CR3 axis in addition to the C3a-C3aR axis.…”
Section: Figurementioning
confidence: 99%
“…Die Fähigkeit zirkulierender hämatopoietischer Stammzellen zum Repopulieren entfernter Knochenmarksregionen durch hämatogene Aussaat ist direkt belegt durch Teilkörperbestrahlungs-und Parabiose-Experimente in der Maus [23][24][25][26][27][28]. Eine Vielzahl von Stimuli, darunter exogene hämatopoietische Wachstumsfaktoren [29], Chemokine [30][31][32][33][34][35][36] und Chemokinrezeptor-Antagonisten [37,38], der myeloische Rebound nach zytoreduktiver Chemotherapie [39,40], Integrinrezeptorblocker [41][42][43], bakterielle Toxine [44][45][46][47], aber auch körperliche Anstrengung [48,49], Tageszeit [50][51][52], adrenerge Signale des autonomen Nervensystems [52][53][54][55][56] oder nicht primär hämatologische pathologische Zustände wie Entzündung [44,57], Gewebeschädigung [58], Komplementaktivierung [59,60], Gerinnungsaktivierung [61], können erhöhte Zahlen zirkulierender Stammzellen induzieren. [30,32,33,…”
Section: Grundlagen Der Biologie Hämatopoietischer Stammzellenunclassified